Performance optimization of solar still employing red-bricks as sensible heat storage material and interfacial evaporation area - S. Mankai; S. Chemkhi; J. Madiouli; F. Ouled Saad; I. Shigidi; J. Sghaier (Case Studies in Thermal Engineering)
Freshwater productivity by solar desalination offers promising solutions for using clean energy, reducing environmental pollution and being cost-effective. However, solar stills require energy storage and evaporation rate improvement to overcome global water demand. In this article, a case study in Kairouan city (Tunisia) is presented: the impact of incorporating hollow-red-bricks into the basin area of single-slope-solar-stills to improve sensible energy storage capacity and water evaporation area by capillarity action was investigated. The study specifically analyses the effect of varying the bricks height over the basin. Therefore, four identical solar distillers were designed and constructed: three systems called modified solar stills integrating hollow bricks with 4 cm, 6 cm and 8 cm heights, and a conventional system. This work included an in-depth examination of energy, exergy, economic and to environmental aspects for both systems. Thus, the use of red-bricks significantly improved water production by 33.84 %, 29.1 % and 28.87 % for MSS-6cm, MSS-4cm and MSS-8cm in comparison to that of the conventional case. Furthermore, the net repayment period and the carbon credit earned were also calculated. The results revealed that 6 cm was the optimal brick height giving a maximum energy payback period of about 100 days and could mitigate 94.26 tons of CO2 emission during its 10 years lifetime.